A comparison of muscle activations during traditional and abbreviated tennis serves - Seeley, M. K.; Uhl, T. L.; McCrory, J.; McGinn, P.; Kibler, W. B.; Shapiro, R. (Sports Biomechanics, 2008)
The abbreviated tennis serve is a relatively novel modification of the traditional serve that has been reported to provide performance advantages over the traditional technique. However, there are limited objective data regarding the benefits and biomechanics of the abbreviated serve; no data exist that describe shoulder muscle activations during the abbreviated serve. The purpose of this study was to compare muscle activations between the traditional and abbreviated serves. Electromyographic data were collected for the anterior and posterior deltoid, infraspinatus, middle trapezius, latissimus dorsi, serratus anterior, and pectoralis major. When muscle activations were compared during each serve phase, no significant differences were observed between the traditional and abbreviated tennis serve techniques, indicating that the traditional and abbreviated serves are similar regarding shoulder muscle activations. These results could have implications for performance of and injury related to the abbreviated versus traditional serve technique. Although the abbreviated serve has anecdotally been described as advantageous, the present data do not indicate any significant advantages or disadvantages in performing the abbreviated serve technique versus the traditional serve.